2015
DOI: 10.1021/acs.analchem.5b00071
|View full text |Cite
|
Sign up to set email alerts
|

Supercharging with m-Nitrobenzyl Alcohol and Propylene Carbonate: Forming Highly Charged Ions with Extended, Near-Linear Conformations

Abstract: The effectiveness of the supercharging reagents m-nitrobenzyl alcohol (m-NBA) and propylene carbonate at producing highly charged protein ions in electrospray ionization is compared. Addition of 5% m-NBA or 15% propylene carbonate increases the average charge of three proteins by ∼21% or ∼23%, respectively, when these ions are formed from denaturing solutions (water/methanol/acetic acid). These results indicate that both reagents are nearly equally effective at supercharging when used at their optimum concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 93 publications
3
61
0
3
Order By: Relevance
“…The gradual increase in size of ions with charge > 8+ is an indicator for an unzipping of the already elongated, presumably helical conformations to even more extended structures [9,21]. In fact, earlier IM-MS studies showed that ions in even higher charge states than the ones investigated here slowly approach the size of the linear form L with a CCS of ~2600 Å 2 [7,9] -the upper size limit for ubiquitin ions. However, IM-MS methods only yield information about the overall size and shape of protein ions, while further structural details, such as the secondary structure, remain elusive.…”
Section: Ubiquitin -From Compact To Stringmentioning
confidence: 59%
See 4 more Smart Citations
“…The gradual increase in size of ions with charge > 8+ is an indicator for an unzipping of the already elongated, presumably helical conformations to even more extended structures [9,21]. In fact, earlier IM-MS studies showed that ions in even higher charge states than the ones investigated here slowly approach the size of the linear form L with a CCS of ~2600 Å 2 [7,9] -the upper size limit for ubiquitin ions. However, IM-MS methods only yield information about the overall size and shape of protein ions, while further structural details, such as the secondary structure, remain elusive.…”
Section: Ubiquitin -From Compact To Stringmentioning
confidence: 59%
“…The theoretical CCS of the folded, native structure (N) and that of the partially unfolded and mostly helical A state (A) found in denaturing solutions are indicated as dashed, vertical lines in Figure 2a, together with the CCS values of two hypothetical structures, an extended, 5 fully α-helical (H) and a fully linear conformation (L) [7]. The gradual increase in size of ions with charge > 8+ is an indicator for an unzipping of the already elongated, presumably helical conformations to even more extended structures [9,21]. In fact, earlier IM-MS studies showed that ions in even higher charge states than the ones investigated here slowly approach the size of the linear form L with a CCS of ~2600 Å 2 [7,9] -the upper size limit for ubiquitin ions.…”
Section: Ubiquitin -From Compact To Stringmentioning
confidence: 98%
See 3 more Smart Citations